Use of molecular marker diversity to increase forage yield in timothy (Phleum pratense L.). Issue 2 (25th December 2012) - Tanaka, Tsuneki; Tamaki, Hiroyuki; Ashikaga, Kazunori; Fujii, Hiroki; Yamada, Toshihiko; Staub, J.
Abstract Molecular marker technologies may provide a tool to overcome the forage yield plateau in timothy (Phleum pratense L.). Therefore, a study was designed to investigate the relationship between marker‐based genetic distance (GD) estimates and yield. Genetic distances were estimated using Dice coefficients framed by 28 simple sequence repeat markers. In Experiment 1, parents with high general combining ability (GCA) from two contrasting first‐generation synthetic strains (exhibiting high and low yields) were compared. Average GDs of each strain were 0.74 (high) and 0.68 (low). These differences indicated that GD may be partially the basis for contrasting yields. In Experiment 2, GDs among 40 parents of a polycross were used for calculating general genetic distance (GGD), which is indicative of their allelic complementation. Analyses revealed a significant (P < 0.01) moderate correlation (r) between GGD and GCA for yield (r = 0.45) and a significant (P < 0.01) residual mean square for the regression of yield on GGD, suggesting that considerable non‐additive effects were associated with GCA. The results are indicative of the potential use of GD estimation for yield improvement in timothy.